Highly Water-Soluble Cyclopentadienyl and Indenyl Molybdenum(II) Complexes - Second Generation of Molybdenum-Based Cytotoxic Agents - Mrózek, Ondřej; Šebestová, Lucie; Vinklárek, Jaromír; Řezáčová, Martina; Eisner, Aleš; Růžičková, Zdeňka; Honzíček, Jan (My University, 2016)
A series of the cyclopentadienyl and indenyl molybdenum compounds bearing alkylammonium functions [(eta(5)-Cp')Mo(CO)(2)(L-N,L-N)][BF4](2) were synthesized and characterized by analytical and spectroscopic methods. The structures of [{eta(5)-C5H4CH2CH2NH(CH2)(5)}Mo(CO)(2)(4,7-Ph-2-phen)][BF4](2) (4,7-Ph-2-phen = 4,7-dipheny1-1,10-phenanthroline) and [(eta(5)-C9H6CH2CH2NHMe2)Mo(CO)(2)(phen)][BF4](2) (phen = 1,10-phenanthroline) were determined by X-ray crystallography. All of the synthesized compounds exhibit high activity against the human leukemia cell lines MOLT-4 and HL-60. They are approximately one order of magnitude more active than cisplatin. This study has proven that the modification of the outer coordination sphere of molybdenum complexes has a strong impact on their activity and may be successfully used for the design of new highly cytotoxic active species.
Cyklopentadienylové a indenylové komplexy molybdenu rozpustné ve vodě - druhá generace cytotoxických sloučenin molybdenu
Keywords: molybdenum; indenyl; cytotoxicity; molybden; indenyl; cytotoxicita